Anticipation, climate change, and movement in Greenland - Nuttall, Mark (Études/Inuit/Studies, 2010)
AbstractDrawing and reflecting on long-term research and fieldwork in Greenland, I seek through this article to broaden the discussion of adaptation, vulnerability, and resilience in the climate change literature to include a focus on anticipation. While adaptation is a reactive response to climate change, anticipation is more about intentionality, action, agency, imagination, possibility, and choice. It is also about being doubtful, unsure, uncertain, fearful, and apprehensive. Through a specific discussion of hunting, I argue that understanding local perceptions, concerns, preparedness and responses to changes in the environment depends on understanding the social and cultural context of anticipation, how people learn to anticipate, and the nature of that anticipation.